The Influence of Intellectual Capital and Characteristics of the Sharia Supervisory Board on the Performance of Islamic Maqashid - Nadila Khoerunisa; Bima Cinintya Pratama; Azmi Fitriati; Annisa Ilma Hartikasari (Jurnal Ekonomi dan Bisnis Digital, 2023)
This study aims to examine the implementation of Islamic maqasid performance in Islamic banks by considering the influence of the aspects of Intellectual Capital (IC) and the Sharia Supervisory Board. This study uses a sample of Islamic banks in Indonesia that are registered with the Financial Services Authority. The number of observational data is 148 data during the 2008-2020 period. To test the research hypothesis used panel data regression model analysis. The analytical tests used in this study were the preliminary test (Breusch-Pagan, likelihood test, hausman test) , diagnostic tests (heteroscedasticity test and autocorrelation test) and hypothesis testing. Based on the results of the three preliminary tests in determining the panel data regression model, this study will use a random effect model . The results of the study reveal that Intellectual Capital (IC) has a positive influence on the performance of Islamic maqashid . Utilization of Intellectual Capital (IC) that is more optimal can improve the performance of higher Islamic banking maqashid sharia.